Skin and pulmonary models using coated bentonite particles for the study of the inflammation evoked by Paracoccidioides brasiliensis antigens in previously immunized mice - Faveri, Julio de [UNESP]; Tamanini, J.; Tonolli, L.; Franco, M. (Oxford University Press (OUP), 1984)
Bentonite particles coated with polysaccharide antigen or crude soluble antigen of Paracoccidioides brasiliensis were injected intradermally or intravenously in mice. In control animals that were not pre-immunized with P. brasiliensis antigens, coated and uncoated bentonite caused minimal and nonspecific inflammation around the cutaneous injection site or around the bentonite thrombi in small lung vessels after intravenous injection. However, in mice previously immunized with P. brasiliensis antigens, the coated bentonite particles boosted the humoral and cellular immune responses to P. brasiliensis and evoked intense inflammatory reactions. Twelve days after intradermal injection, the inflammatory reaction around the bentonite was rich in neutrophils, macrophages, lymphocytes and plasma cells associated with young granulation tissue. In intravenously injected mice, the pulmonary inflammation was maximal at day 2, and was characterized by a florid neutrophilic and macrophagic cellular infiltration around bentonite thrombi; in some foci, there was incipient organization to mature granuloma. However, in both models, there was no formation of epithelioid granulomata, demonstrating that in paracoccidioidomycosis cellular immunity alone, without the presence of intact micro-organisms, may not be enough for the development of this type of granuloma.
Keywords: antigen; animal experiment; fungus; mouse; nonhuman; paracoccidioides brasiliensis; Animal; Antigens, Fungal; Bentonite; Disease Models, Animal; Fungi; Hypersensitivity, Delayed; Injections, Intradermal; Injections, Intravenous; Lung; Mice; Mice, Inbred Strains; Paracoccidioides; Paracoccidioidomycosis; Skin; Support, Non-U.S. Gov't